Need for touch and haptic imagery: an investigation in online fashion shopping - Silva, Susana C. (2021)
Previous research has found evidence that, due to the lack of sensory experience, shoppers are reluctant to purchase a garment online. Despite the importance of identifying possible compensatory cues for touch information, a lack of attention to this issue has been recognized in the literature. On this premise, this study addresses this research agenda to explain the mechanism by which information presentation influences customers' cognitive evaluations and behavioral responses and the role of individual differences in terms of need for touch (NFT). Specifically, drawing on the Stimulus-Organism-Response (S–O-R) paradigm, the study hypothesizes a model investigating whether verbal and pictorial information presentation affect haptic imagery, which in turn is supposed to influence behavioral responses (purchase intention), through a customer's cognitive evaluation (perceived product quality). To validate the research framework, a task-based online experiment was performed. Participants were requested to simulate a purchase experience on an online apparel retailer, after which they completed a questionnaire; 264 valid responses were received. The results support verbal haptic rather than pictorial information as a mechanism influencing haptic imagery and consequently behavioral responses. With regard to NFT, however, the expected moderating effect between haptic imagery, perceived product quality, and purchase intention was not supported.